Versal deformations of invariant subspaces - Ferrer, Josep; Puerta, Ferran (Linear algebra and its applications, 2001)
We describe a miniversal deformation of invariant subspaces (with regard to a fixed endomorphism) by means of a technique which can be applied to obtain explicitly miniversal deformations in a general orbit space. In addition, we present an application to the problem of classifying invariant subspaces.